Sensorless Rotor Position Detection of PMSM for Automotive Application (Hungarian Journal of Industry and Chemistry, 2010)
For correct operation of the permanent magnet synchronous motors is essential the knowledge of the rotor position, which is usually given by Hall-sensors, encoders or resolvers. The aim of the present work is to set up such a general motor model, which takes into consideration the anisotropies in the magnetic structure of the motor.
Keywords: rotor position estimation; PMSM motor model; model validation; sensorless control methods